(untitled) (Ustozlar uchun, 2025)
This article analyzes the dominant role of English in modern science, its significance in global scholarly communication, as well as the issues related to enriching scientific terminology in the Uzbek language. The study examines the main approaches to translating terminology, the importance of standardization, the need to develop scientific translation schools, and the expansion of digital scientific content. The findings demonstrate that effective use of English and the development of the Uzbek scientific language are complementary processes crucial for the advancement of national science.